English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-15 04:29:12 · 5 answers · asked by shelia.boswell 1 in Science & Mathematics Mathematics

5 answers

(-2+2)(-4-3) =

0(-7) =

0.

2007-09-15 04:35:38 · answer #1 · answered by Anonymous · 0 0

0

since x + 2 = -2 + 2 = 0

2007-09-15 11:51:58 · answer #2 · answered by Beardo 7 · 0 0

F(-2) = (-2 + 2) (-4 - 3) = (0) (-7) = 0

2007-09-15 11:43:13 · answer #3 · answered by Dale E 3 · 0 0

f(-2) = ((-2) + 2)(2(-2) - 3)
= (-2 + 2)(-4 -3)
= 8 + 6 -8 -6
= 0

2007-09-15 11:36:55 · answer #4 · answered by skenasis 2 · 0 0

ok im goin with its 0 cuz the guy above me said so and i want 2 points.

2007-09-15 11:37:17 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers